Associations Between Psychological and Immunological Variables in Chronic Fatigue Syndrome/Myalgic Encephalomyelitis: A Systematic Review - Raanes, Emilie F. W.; Stiles, Tore C. (Frontiers in Psychiatry, 2021)
Little emphasis has been given to the fact that various psychological processes and behaviors in chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) have neural correlates that affect – and are affected by – the immune system. The aim of this paper is to provide a systematic review of the literature on cross-sectional and longitudinal associations between psychological and immunological variables/changes in CFS/ME. The systematic literature search was conducted on Dec 10, 2020 using PubMed. Original research studies investigating associations between a predefined set of psychological and immunological variables in CFS/ME were included. Specifically, the review was focused on studies examining the following psychological variables: executive function, emotion regulation, interpersonal function, sleep, mental health, anxiety, depression and/or other psychiatric symptoms. In terms of immunological variables, studies investigating interleukin (IL)-1, IL-2, IL-4, IL-6, tumor necrosis factor (TNF), CD4+ and/or CD8+ were included. Besides original research papers, other potentially relevant papers (e.g., literature reviews) were carefully read and reference lists were checked in order to identify any additional relevant studies. Available data was summarized in text and tables. The literature search identified 897 potentially relevant papers. Ultimately, 14 studies (807 participants in total) were included in the review of which only two were longitudinal in nature. The review indicated that executive function is associated with IL-1 and IL-6 and interpersonal function is associated with IL-6 and TNF-. Further, the available data suggested that emotion regulation is associated with IL-2 and sleep is associated with IL-1, IL-6, TNF- and IL-2. Interestingly, poorer emotion regulation, interpersonal function and sleep have all been found to be associated with higher cytokine levels. Executive function has shown both positive and negative relationships with cytokines and among these psychological constructs, it is also the only one that has been found to be associated with CD4+ and CD8+ counts/percentages. Correlations exist between psychological and immunological variables in CFS/ME. However, there are few consistent findings and there is almost a complete lack of longitudinal studies. This review points to a gap in existing CFS/ME research and hopefully, it will inspire to the generation of innovative, psychoneuroimmunological hypotheses within the CFS/ME research field.